Eccentricity effects in vision and attention. (November 2016) - Staugaard, Camilla Funch; Petersen, Anders; Vangkilde, Signe
Abstract: Stimulus eccentricity affects visual processing in multiple ways. Performance on a visual task is often better when target stimuli are presented near or at the fovea compared to the retinal periphery. For instance, reaction times and error rates are often reported to increase with increasing eccentricity. Such findings have been interpreted as purely visual, reflecting neurophysiological differences in central and peripheral vision, as well as attentional, reflecting a central bias in the allocation of attentional resources. Other findings indicate that in some cases, information from the periphery is preferentially processed. Specifically, it has been suggested that visual processing speed increases with increasing stimulus eccentricity, and that this positive correlation is reduced, but not eliminated, when the amount of cortex activated by a stimulus is kept constant by magnifying peripheral stimuli (Carrasco et al., 2003). In this study, we investigated effects of eccentricity on visual attentional capacity with and without magnification, using computational modeling based on Bundesen's (1990) theory of visual attention. Our results suggest a general decrease in attentional capacity with increasing stimulus eccentricity, irrespective of magnification. We discuss these results in relation to the physiology of the visual system, the use of different paradigms for investigating visual perception across the visual field, and the use of different stimulus materials (e.g. Gabor patches vs. letters). Highlights: Visual capacity for letter stimuli decreases toward the visual periphery. The decrease in visual capacity is irrespective of cortical magnification. Peripheral performance might depend on the specific stimuli and task demands.